2009
DOI: 10.1007/978-3-642-04271-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Prediction of Brain Shift Using Nonlinear Finite Element Algorithms

Abstract: Abstract. Patient-specific biomechanical models implemented using specialized nonlinear (i.e. taking into account material and geometric nonlinearities) finite element procedures were applied to predict the deformation field within the brain for five cases of craniotomy-induced brain shift. The procedures utilize the Total Lagrangian formulation with explicit time stepping. The loading was defined by prescribing deformations on the brain surface under the craniotomy. Application of the computed deformation fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 22 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…We (and others) 3,5,8,9,11,16,18,20,23,24,28 have developed image-guidance updating frameworks formulated around computational model–based assimilation of brain shift measurement data acquired intraoperatively with minimally disruptive imaging tools. The accuracy and performance of these approaches have been evaluated in clinical cases, 16,21,24,28 but most analyses have been retrospective to surgery, and updated images have not routinely been generated in the OR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We (and others) 3,5,8,9,11,16,18,20,23,24,28 have developed image-guidance updating frameworks formulated around computational model–based assimilation of brain shift measurement data acquired intraoperatively with minimally disruptive imaging tools. The accuracy and performance of these approaches have been evaluated in clinical cases, 16,21,24,28 but most analyses have been retrospective to surgery, and updated images have not routinely been generated in the OR.…”
mentioning
confidence: 99%
“…The accuracy and performance of these approaches have been evaluated in clinical cases, 16,21,24,28 but most analyses have been retrospective to surgery, and updated images have not routinely been generated in the OR. In recent work by Sun et al, 24 a brain shift compensation system involving intraoperative laser range scanning was described to perform brain shift correction intraoperatively.…”
mentioning
confidence: 99%
“…There have been major advances in real time simulations of deformable soft tissues 94 and brain deformation. 36,37 The trade-off between computational time and accuracy is a major challenge, although recently a method of computing fractional flow reserve (FFR) has reduced the computational time from 5 days to a matter of seconds. 74 Perhaps the biggest challenge is to provide enough evidence that patient-specific modelling can benefit patients of AoD.…”
Section: Real Time and Large Scale Simulationsmentioning
confidence: 99%
“…When we created more elements in a certain volume, the computations rapidly increased in a nonlinear manner, whereas the final precision slightly changed. FEM-based studies [16,18] have shown that a total of 15,000 elements were created to reconstruct an entire human brain. It is therefore reasonable that a total of 3718 elements were sufficient to create our animal model, which presented a much smaller brain volume (approximately1/8).…”
Section: Initializing Fe Linear Elastic Modelmentioning
confidence: 99%
“…More recently, powerful GPU processors make it possible that nonlinear FEMs can be used for estimating brain shift [18]. However, all studies based on FEM are focused on estimating brain deformation after craniotomy, due to disruption of nodes in the model, none of them models the resections.…”
Section: Introductionmentioning
confidence: 99%